Evaluation Of Staff And Patient ryRadiation Doses In Orthopedic Surge - Badria hbeeb alla mohammed Alhassan; Abdelmoneim Adam Mohamed Sulieman; Ikhlas Abdelaziz Hassan (Asian Journal of Medical Radiological Research, 2015)
Orthopedists are exposed to considerable radiation dose during orthopedic surgeries procedures. The staffs are not well trained in radiation protection aspects and its related risks. In Sudan, no regular monitoring services are provided for all staff in radiology or interventional personnel. Therefore, it is mandatory to measure staff and patient exposure in order to radiology departments. The main objectives of this study are to measure the radiation dose to patients and staff during (i) Dynamic Hip Screw (DHS) (ii)Dynamic Canula Screw (DCS), estimate the risk of the aforementioned procedures and to evaluate entrance surface dose (ESD), organ and surface dose to specific radiosensitive patient's organs. The measurements were performed in two different departments: (i) Omdurman Military Hospital and (ii) Mulazimeen Hospital. The dose was measured unprotected organs of staff and patient as well as scattering radiation. Calibrated Thermo luminescence dosimeters (TLD-GR200) of lithium fluoride (LiF: Mg, Cu,P) were used for ESD measurements. TLD signal will be obtained using automatic TLD Reader model (PLC3). The mean patients' doses were 0.46 mGy and 0.07 for DHS and DCS procedures, respectively. The mean staff doses for thyroid and chest were 4.69 mGy and 1.21 mGy per procedure, at the same order. The mean radiation dose for staff was higher in DHS compared to DCS. This can be attributed to the long fluoroscopic exposures due to the complication of the procedures. Efforts should be made to reduce radiation exposure to orthopedic patients, and operating surgeons especially those undergoing spinal surgery. Well training, continuous monitoring and rich knowledge about hazard among orthopedist are starting steps to reduce radiation risk.